PENGEMBANGAN MEDIA PEMBELAJARAN DIORAMA MENARA EKOSISTEM PADA MATERI HARMONI DALAM EKOSISTEM KELAS V SDN 2 MRANTI PURWOREJO - Frizka Helen Cornelia; Titi Anjarini; Muhammad Ferdian Syaifullah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the limited availability of instructional media capable of presenting ecosystem concepts in a concrete and engaging manner, resulting in less effective science and social studies (IPAS) learning on the topic of Harmony in Ecosystems. The objectives of this study were to develop the Ecosystem Tower Diorama learning media for fifth-grade students at SDN 2 Mranti and to determine its feasibility as a learning medium. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects included five students in the limited trial and twenty-four students in the field trial. Data were collected through observations, interviews, questionnaires, and tests and analyzed using descriptive quantitative and qualitative techniques. The results indicated that the Ecosystem Tower Diorama learning media was successfully developed and met the feasibility criteria for classroom implementation. Validation results reached 76.9% from the material expert, 100% from the media expert, and 93.75% from the practitioner, all categorized as highly feasible. Student responses showed a practicality score of 85% in the limited trial and 90.49% in the field trial, both categorized as highly practical. Learning outcomes based on the pretest and posttest showed improvement scores of 64% in the limited trial and 70.54% in the field trial, both classified as high. Therefore, based on its feasibility, practicality, and effectiveness, the Ecosystem Tower Diorama is considered suitable for use as an instructional medium for the Harmony in Ecosystems topic in fifth-grade elementary school learning.